Aggressive Behavior and Its Relation to Independence among Cochlear Students at Primary Stage (Journal Of Educational and Psychological Researches, 2025)
This research aims to identify the relationship between aggressive behavior and independence. To achieve this objective, the researcher developed two scales to measure aggressive behavior and independence among a sample of 146 mothers of children with cochlear implants, whose ages ranged from 6 to 12 years. The researchers adopted the descriptive analytical method. The results showed that the level of aggressive behavior was low (44.13%). The level of independence was high (81.36%). Moreover, the results showed that there is a significant negative correlation between aggressive behavior and independence. The results also showed that there are no statistically significant differences in the averages of aggressive behavior and independence among cochlear implant students due to the child's sex, the child's age, or the beginning of cochlear implantation. The research recommended the need for continuous psychological support and social activities in modifying the aggressive behavior and establishing independent behavior of children with cochlear implants through the family’s roles.